Pengaruh Makanan Kaya Gizi (KAYAZI) sebagai Variasi Diet Energi Protein Tinggi terhadap Daya Terima Makanan Pasien Covid-19 - Anggraeny Putri, Nur; Ruliana, Ruliana; Yulianingrum, Chintya (RSUD Dr. Saiful Anwar Province of East Java, 2022)
Background: Energy-Protein High (EPH) diet given as nutrition support in infection cases, including Covid-19. Low diet acceptance impact the patient’s recovery; but it can be solved by modified the diet menu. KAYAZI (Makanan Kaya Gizi) as innovation of EPH diet menu can be applied too for covid-19’s patients. Objective: Knowing the effect of KAYAZI as EPH diet variation on food acceptability in terms of food waste and dietary satisfaction in PUS at General Hospital dr. Saiful Anwar Malang. Method: Quasy Experimental with purposive sampling. Total 33 samples for each groups (standard-TKTP diet; KAYAZI diet) based on inclusion-exclusion criteria. Food waste data obtained from observing and filling in Comstock visual form. Dietary satisfaction data obtained from filling out Likert-scale questionnaire in hedonic-scale test. Data processed by software SPSS ver.16, with hypothesis testing nonparametric Mann-Whitney test (p value <0.05). Result: percentage of food waste from KAYAZI was smaller (10.5%) than TKTP diet (25.03%); the mean value of KAYAZI satisfaction level was higher in all assessment categories than the TKTP diet. From the Mann-Whitney, p value <0.05 on food waste and dietary satisfaction for parameters: aroma, taste, color, shape, food containers and cutlery. Meanwhile, dietary satisfaction on parameters of texture and way of food presenting, the value of p> 0.05. Conclusion: The provision of KAYAZI as diet variation affects food acceptability in term of food waste and dietary satisfaction for parameters: aroma, taste, color, shape, food containers and cutlery. But it has no effect in food texture parameter and way of food presenting.